Immune thrombocytopenic purpura - Abir Zainal; Amr Salama; Richard Alweis (Greater Baltimore Medical Center, 2019)
Immune thrombocytopenic purpura (ITP) is a bleeding disorder characterized by isolated thrombocytopenia (platelet count <150,000 u/L), which is not associated with a systemic illness. ITP is reported in approximately 2 per 100,000 adults. The mean age of diagnosis is 50 years. ITP is more common in females of childbearing age and in pregnancy. In adults, the course is more chronic although spontaneous remission can also occur within months of initial diagnosis. A thorough and timely workup of thrombocytopenia is imperative to rule out other differentials of ITP as it is considered a diagnosis of exclusion. Primary care physicians encounter patients who exhibit signs of thrombocytopenia such as petechiae or purpura on a regular basis. A high index of clinical suspicion is required to accurately diagnose ITP and commence the appropriate treatment including glucocorticoids to increase the chances of a favorable prognosis as described by the authors.